Tosaka Jun : a critical reader - Tosaka, Jun, 1900-1945 (Cornell East Asia series ;, 2013)
Tosaka Jun (1900-1945) was one of modern Japan's most unique, urgent, and important critics of capitalism, Japanese imperialism, the emperor system, 'Japanism', and everyday life in imperial Japan. A philosopher trained at Kyoto University, Tosaka made major contributions to the advancement of Marxism and historical materialism in Japan, most notably as the central figure at the Yuibutsuron kenkyūkai. His writings reveal a true renaissance thinker, moving from the history and philosophy of science to profound and brilliant studies of everyday life, media, fascism, militarism, and what Tosaka called 'The Japanese ideology'. His Marxist philosophy especially sought to move beyond a mechanistic Marxism, and to criticize the diverse ways in which cultural productions of the nation, the empire, and 'Japan', were deeply implicated in capitalist exploitation, imperialist domination in Asia, and fascist war.